A systematic review of the toxic potential of parabens in fish - Dasmahapatra, Asok K.; Chatterjee, Joydeep; Tchounwou, Paul B. (Frontiers in Toxicology, 2024)
Parabens are the most prevalent ingredients in cosmetics and personal care products (PCPs). They are colorless and tasteless and exhibit good stability when combined with other components. Because of these unique physicochemical properties, they are extensively used as antimicrobial and antifungal agents. Their release into the aquatic ecosystem poses potential threats to aquatic organisms, including fish. We conducted an electronic search in PubMed (http://www.ncbi.nlm.nih.gov/pubmed) using the search term parabens and fish and sorted 93 articles consisting of methyl paraben (MTP), ethyl paraben (ETP), propyl paraben (PPP), butyl paraben (BTP), and benzyl paraben (BNP) in several fish species. Furthermore, we confined our search to six fish species (common carp, Cyprinus carpio; fathead minnows, Pimephales promelas; Japanese medaka, Oryzias latipes; rainbow trout, Oncorhynchus mykiss; Nile tilapia, Oreochromis niloticus; and zebrafish, Danio rerio) and four common parabens (MTP, ETP, PPP, and BTP) and sorted 48 articles for review. Our search indicates that among all six fish, zebrafish was the most studied fish and the MTP was the most tested paraben in fish. Moreover, depending on the alkyl chain length and linearity, long-chained parabens were more toxic than the parabens with short chains. Parabens can be considered endocrine disruptors (EDs), targeting estrogen-androgen-thyroid-steroidogenesis (EATS) pathways, blocking the development and growth of gametes, and causing intergenerational toxicity to impact the viability of offspring/larvae. Paraben exposure can also induce behavioral changes and nervous system disorders in fish. Although the USEPA and EU limit the use of parabens in cosmetics and pharmaceuticals, their prolonged persistence in the environment may pose an additional health risk to humans.